2023
DOI: 10.1002/art.42463
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Disease‐Related Proteins in Joints as Novel Biomarkers for the Diagnosis of Rheumatoid Arthritis

Abstract: Objective. This study was undertaken to develop and characterize a multiplex immunoassay for detection of autoantibodies against peptides derived from proteins known to play a role in development of arthritis and that are also expressed in joints.Methods. We selected peptides from the human counterpart of proteins expressed in the joints, based on mouse models that showed these to be targeted by pathogenic or regulatory antibodies in vivo. Using bead-based flow immunoassays measuring IgG antibodies, we selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The above results indicated that the detection subtype of RF was an important supplementary test for seronegative RA. [ 15 ] In this study, results indicated that although RF, ESR, CCP, RF-IgA, RF-IgM, RA33, and C3 were significantly higher in ERA patients, only RF and ESR had significant differences in the independent prediction of ERA. However, this nomogram model suggested that RA33 had certain value for the combined diagnosis of ERA in addition to RF and ESR.…”
Section: Discussionmentioning
confidence: 60%
“…The above results indicated that the detection subtype of RF was an important supplementary test for seronegative RA. [ 15 ] In this study, results indicated that although RF, ESR, CCP, RF-IgA, RF-IgM, RA33, and C3 were significantly higher in ERA patients, only RF and ESR had significant differences in the independent prediction of ERA. However, this nomogram model suggested that RA33 had certain value for the combined diagnosis of ERA in addition to RF and ESR.…”
Section: Discussionmentioning
confidence: 60%
“…Thus, the aetiological triggering is likely an event predating the induction of RF and ACPA. Furthermore, based on the binding pattern by E4 on large peptide libraries tested in cohorts of early and established RA, we assume that a substantial fraction of circulating ACPA will be protective 21 47 48. However, a peptide library in vitro only poorly reflects the specificity of the antibodies in vivo, which is remarkably more restrictive.…”
Section: The In Vivo Role Of Promiscuous Acpamentioning
confidence: 99%
“…In fact, it has been reported that the standard CCP2 assay does not detect up to 20% of seronegative patients with antibodies binding to other citrullinated antigens,49 and the fact that most ACPA-positive individuals without RA never developed RA further indicates that CCP2 might not reflect the ideal in vivo target. Thus, although the CCP2 test has been a useful diagnostic tool for clinical RA, a new approach using various RA-related citrullinated proteins/peptides defined in vivo may be helpful to capture more seronegative RA,48 identify more subgroups with RA, contribute to preclinical RA diagnosis or perhaps distinguish antibody responses (ie, protective vs non-protective). In addition, the antibody response is polyclonal, and antibodies with different specificities carrying different functions are mixed.…”
Section: The In Vivo Role Of Promiscuous Acpamentioning
confidence: 99%
“…Furthermore, antibodies to an outer mitochondrial membrane protein, MFN1, predicted the development of erosive disease in seronegative RA. A multiplex immunoassay with peptides from disease-related proteins in joints of RA patients detected a set of five peptides composed principally by new ACPA (cross)reactivities but also included a peptide without citrulline, that identified 22.5% (n=125) of seronegative patients (n=556) with 99% specificity (39).…”
Section: Novel Antibodiesmentioning
confidence: 99%